2015
DOI: 10.1016/j.jval.2015.09.1864
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy-Effectiveness-Gap – Extent, Causes And Implications

Abstract: A567assess whether the drug costs stated in BIA matches to real costs. Methods: Twelve HID obtained CED in 2013. The drug costs were identified in BIA of eleven HID. Real costs of General Health Insurance Company (VZP) were found out for each HID in the first year of therapy. As VZP holds 60% of the health insurance market, the data were extrapolated to the whole population. The differences between estimated and real drug costs were analysed and a correlation between this differences and drug characteristics j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The difference in outcomes between phase 3 clinical trial patients and RWPs is known as the efficacy-effectiveness gap. 25,26 Accounting for individual factors that affect dose response can maximize effectiveness and minimize AEs in RWPs. 27 Given our study findings, we designed and executed a prospective study (NCT03885830) that seeks to associate effectiveness and toxicity outcomes with TKI plasma concentrations, with the long-term goal of guiding TKI dose selection based on RWP factors.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in outcomes between phase 3 clinical trial patients and RWPs is known as the efficacy-effectiveness gap. 25,26 Accounting for individual factors that affect dose response can maximize effectiveness and minimize AEs in RWPs. 27 Given our study findings, we designed and executed a prospective study (NCT03885830) that seeks to associate effectiveness and toxicity outcomes with TKI plasma concentrations, with the long-term goal of guiding TKI dose selection based on RWP factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, a network meta-analysis of clinical trials did not show higher cardiovascular risks of low-dose diuretics as first-line antihypertensive treatment compared to β-blockers, angiotensin-converting enzyme inhibitors, calcium channel blockers, alpha-blockers, and angiotensin receptor blockers; rather the opposite was observed [41]. The divergent results can have several reasons: the efficacy-effectiveness gap of clinical trials [42], non-comparable study populations, or an insufficient control for confounding in observational studies. The last point is supported by the fact that our analysis was limited by insufficient control for confounders, such as heart failure and CHD both presenting a higher baseline cardiovascular risk for the affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, uptake of the IPTp in Uganda is encumbered by several barriers categorized under the six building blocks of the health system, namely leadership/governance, health nancing, medicines and technologies, health information system, human resources, and service delivery and health service user-related barriers. Use of the PTRC analysis tool provided the MAPD team with systematic insights into the barriers effecting program implementation and possible solutions to address them to close the e cacy-effectiveness gap for IPTp [22]. Use of the PTRC analysis tool identi ed similar barriers in a narrative synthesis by Olaleye and Walker (2020), which found that factors effecting the supply and demand for IPTp services involve all pillars of the health system across sub-Saharan Africa [23].…”
Section: Improved Sp Supply Chain Managementmentioning
confidence: 99%